Effect of Supplementation of L- Threonine on Growth Performance and Carcass Characteristics in Japanese Quail - Namdeo, Pramod; Tiwari, S P; Doneria, Raina; Dubey, Meenu; Yadav, Rajkumar (Indian Journal of Animal Nutrition, 2019)
Day old Japanese quail chicks (n = 150) were randomly allocated to 5 groups with three replicates of 10 birds in each. Five types of diets were prepared containing 24, 23, 22, 21 and 20 % crude protein for group T1 to T5 respectively. L-threonine was supplemented in the diet @ 0.0 %, 0.05%, 0.1%, 0.15% and 0.2% from group T1- T5 respectively. Body weight at 28 d was significantly (P